The Road to Changes in the Preparation of Law No. 15 of 2019 over Law No. 12 of 2011 - Akhmad Zaki Yamani; Hasani Zakiri (Publikasi Indonesia, 2024)
This article analyzes the changes that have occurred in drafting legislation in Indonesia through Law No. 15 of 2019 as an amendment to Law No. 12 of 2011. This research evaluates the impact of these changes on public participation, transparency, and regulatory quality. The findings indicate increased public participation, stronger oversight, and improved regulatory quality. The implications of these changes in legal and social contexts are also discussed, along with recommendations for further refinement in drafting legislation in the future.